Respon tanaman Kedelai terhadap pemupukan kombinasi bio-slurry dengan urea - Reza Mas Indrawan; Yafizham Yafizham; Sutarno Sutarno (Department of Agriculture, Animal and Agricultural Sciences, Diponegoro University, Semara, 2018)
The research aimed to study the effect of combination fertilizer by bio-slurryand urea on the growth and yield of soybean. The experiment was assigned in monofactor randomized complete block design with treatment P0 (Control, without fertilizer), P1 (Bio-slurry10 t/ha + Urea 25 kg/ha), P2 (Bio-slurry10 t/ha + Urea 50 kg/ha), P3 (Bio-slurry10 t/ha + Urea 75 kg/ha), P4 (Bio-slurry10 t/ha + Urea 100 kg/ha), P5 (Bio-slurry10 t/ha). Each treatment was replicated five times. Parameters measured were plant height, leaf number, plant dry matter, 100 seeds weight, and nitrogen total of soybean’s stover. Data were subjected to anova and followed by DMRT. The result showed that combination by bioslurry with urea has incrased growth and yield of soybean significantly (P<0,05). Bio-slurry + urea 50 kg/ha has increased high plant (28.10 cm) and leave number (8.48 leaves) higher compared to another treatments. Bio-slurry + urea 25 kg/ha non-significantly different with bio-slurry + urea 50 kg/ha on dry matter and 100 seeds weight, although higher than another treatments. Nitrogen total of stover of 62.88 g/plant has resulted by bio-slurry + urea 25 kg/ha which was higher than other treatments, but non-significantly different with bio-slurry + urea 50 kg/ha (50.63 g/plant). Keyword : Bio-slurry, combination, growth, soybean, urea, yield